Antibiotic Susceptibility Pattern of Nalidixic Acid Resistant Salmonella Isolates in Shree Birendra Hospital Chhauni (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study was aimed to know the prevalence of Nalidixic acid resistant Salmonella isolates and their antibiotic susceptibility pattern.Methods: A total of 4619 febrile patients suspecting the cases of typhoid fever by clinician, attending at Shree Birendra hospital during May- November 2013 were subjected to culture. Blood sample (5ml) was collected from the suspected cases and inoculated immediately into 45ml of Brain heart infusion broth (BHI) and further processed for the identification of Salmonella Typhi and S. Paratyphi. Antimicrobial susceptibility pattern of S. Typhi and S. Paratyphi isolates were determined by the modified Kirby-Bauer disc diffusion method.Results: Out of 4619 blood sample, 8.7% (n= 403) sample were culture positive. Among culture positive, 66.3%(n=267) cases were S. Typhi, 26.1% (n=105) cases were S. Paratyphi and 7.7% (n=31) were other than Salmonella isolates respectively. Out of 372 Salmonella isolates, most of the S. Typhi isolates i.e. 95.51%(n=255) and S. Paratyphi isolates i.e. 97.14%(n=102) are highly resistant to nalidixic acid. Most of these isolates were also found resistant to ciprofloxacin and ofloxacin.Conclusion: Therefore, screening of nalidixic acid susceptibility might be done prior to prescribe the drug for the treatment of enteric fever.